Student veteran experiences of transition during an unanticipated period of disruption - Foster, Alaina Renee (Kansas State University, 2023)
Student veterans face a multitude of transitions throughout their life, with the initial transition into the military as a civilian, the possibility of multiple transitions throughout their enlistment, and the transition from military service to readjusting to life as a civilian following discharge. As veterans reintegrate into society, some choose to pursue higher education. While student veterans experience anticipated transition, the unanticipated transitions cause one to question how “student” veterans experience the unexpected. This qualitative phenomenological study aimed to understand how student veterans experienced transition while enrolled in community college courses during an unanticipated period of disruption. The researcher selected Cuyahoga Community College (Tri-C) in Cleveland, Ohio, as the study’s host site. The study focused on how student veterans experienced a rapid change in course delivery generated by the COVID-19 pandemic’s disruption to higher education during the 2020 spring semester. Using semi-structured interviews, the researcher aimed to understand how student veterans defined the experience of unanticipated disruption while enrolled in community college classes and the successful strategies used to navigate any decisions made during the transition. The researcher guided the study using Schlossberg’s (1981) Adult Transition Theory. Schlossberg’s theory was selected because it has a four-step process of defining how adults cope with transition called the 4S System. The researcher aligned the interview questions with the 4S System to understand how student veterans experienced unanticipated transition.
Keywords: Student veterans; Students in transition